Tetrabutyl Ammonium Salts of Keggin-Type Vanadium-Substituted Phosphomolybdates and Phosphotungstates for Selective Aerobic Catalytic Oxidation of Benzyl Alcohol - Díaz, Juan (2022)
A series of tetrabutyl ammonium (TBA) salts of V-included Keggin-type polyoxoanions with W (TBA4 PW11 V1 O40 and TBA5 PW10 V2 O40) and Mo (TBA4 PMo11 V1 O40 and TBA5 PMo10 V2 O40) as addenda atoms were prepared using a hydrothermal method. These synthesized materials were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), UV-Vis diffuse reflectance (DRS UV-Vis), thermogravimetric analysis (TGA), CHN elemental analysis (EA), inductively coupled plasma spectrometry (ICP-MS), and N2 physisorption techniques to assess their physicochemical/textural properties and correlate them with their catalytic performances. According to FT-IR and DRS UV-Vis, (PVX W(Mo)12−X O40)(3+X)− anions are the main species present in the TBA salts. Additionally, CHN-EA and ICP-MS revealed that the desired stoichiometry was obtained. Their catalytic activities in the liquid-phase aerobic oxidation of benzyl alcohol to benzaldehyde were studied at 5 bar of O2 at 170◦ C. Independently of the addenda atom nature, the catalytic activity increased with the number of V in the Keggin anion structure. For both series of catalysts, TBA salts of polyoxometalates with the highest V-substitution degree (TBA5 PMo10 V2 O40 and TBA5 PW10 V2 O40) showed higher activity. The maximum benzyl alcohol conversions obtained were 93% and 97% using (TBA)5 PMo10 V2 O40 and (TBA)5 PW10 V2 O40 as catalysts, respectively. In all the cases, the selectivity toward benzaldehyde was higher than 99%.